Activity and reproduction inMegalobulimus paranaguensis(Gastropoda, Eupulmonata): implications for conservation in captivity for a South American land snail - Miranda, Marcel Sabino; Boas Correia, Lucas Vilas [UNESP]; Pecora, Iracy Lea [UNESP] (Taylor & Francis Ltd, 2020)
In South America,Megalobulimusincludes a number of threatened species, as well the largest land snails on the continent. The activity patterns and reproductive aspects of this group have not been documented. This work describes the daily and seasonal activity patterns and reproduction ofM. paranaguensis. We maintained specimens in the laboratory for one year, and we quantified their behaviour for one hour at four different times of the day (0 h, 6 h, 12 h and 18 h) during three days in four months (August, September, April and May). The number of postures, hatching rate, time of hatching since oviposition and mortality rate among juveniles for each month were also quantified.Megalobulimus paranaguensiswas more active in August, and had a egg laying peak one month after. Fifty-one eggs were laid by 12 captive individuals throughout the year, with a mean value of 4.25 eggs per individual. The hatching rate was 80.39%, and the time of hatching since oviposition was 56.7 +/- 4.3 days. In two eggs, we observed the presence of twins. The mortality rate among juveniles was low (9.30%) indicating that rearing land snails in captivity has the potential to be an important and viable tool for the management and conservation of these organisms.
Keywords: Behaviour; hatching rate; Arua-do-mato; fauna management; mortality